Eradication of Bovine Mastitis Caused by the Pathogenic Microalga Prototheca bovis on a Dairy Cattle Farm: A Case Report - Monika Beinhauerova; Monika Moravkova; Ruzena Seydlova; Magdalena Crhanova (Microbiology Research, 2023)
The achlorophyllous unicellular microalga of the genus Prototheca, a causative agent of bovine mammary gland infection, is receiving increasing attention in the field of veterinary medicine. Mastitis caused by these algae leads to significant economic losses for farmers worldwide and represents a source of threat to raw milk quality and dairy food-chain safety. This case report describes an outbreak of bovine mastitis in dairy cattle caused by Prototheca bovis and the on-farm practices that resulted in the recovery of the affected herd and elimination of the presence of Prototheca spp. in the farm environment. Effective management strategies that played a crucial role in protothecosis eradication included regular screening, timely identification, strict separation of Prototheca-positive cows, a change of housing regime associated with the utilisation of straw mattresses and removal of deep bedding and, finally, the introduction of intermediate disinfection of teat cups with peracetic acid to prevent the spread of infection to other healthy individuals. The eradication process lasted approximately three years and required the removal of 139 cows from the farm. The corrective and preventive measures described in this case report provide guidance to farmers on how to successfully deal with protothecal mastitis on farms.